Liquid-liquid equilibria of binary systems {benzene+[x-Mim][NTf2] ionic liquid}: Experimental data and thermodynamic modeling using a group contribution equation of state - Emilio J. González (2014)
Liquid-liquid equilibrium (LLE) data for binary mixtures {benzene (1) + ionic liquid (2)} were measured at atmospheric pressure from 293.15K to 333.15K. The ionic liquids (ILs) studied were 1-ethyl- and 1-hexyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide, ([EMim][NTf2] and [HMim][NTf2]). Furthermore, the group contribution equation of state (GC-EoS) was applied to model the phase behavior of mixtures of hydrocarbons with different members of the homologous family 1-alkyl-3- methylimidazolium bis(trifluoromethylsulfonyl)imide, [x-Mim][NTf2]. New pure group parameters for the ionic liquid functional group (MimNTf2) and interaction parameters between this group and the paraffin (CH3, CH2) and aromatic (ACH) groups are reported. The GC-EOS extended with the new parameters was applied to predict LLE and VLE of binary mixtures {benzene + x-MimNTf2} and LLE of ternary systems {n-hexane + benzene + [x-Mim][NTf2]}. The results show thatthe GC-EOS is capable of predicting the phase behavior of this kind of mixtures with reasonable accuracy.